Commercializing Academic Research: The Quality of Faculty Patenting - Cédric Schneider; Katrin Hussinger; Dirk Czarnitzki (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2008)
The knowledge produced by academic scientists has been identified as a potential key driver of technological progress. Recent policies in Europe aim at increasing commercially orientated activities in academe. Based on a sample of German scientists across all fields of science we investigate the importance of academic patenting. Our findings suggest that academic involvement in patenting results in greater knowledge externalities, as academic patents appear to generate more forward citations. We also find that in the European context of changing research objectives and funding sources since the mid-90?s, the ?importance? of academic patents declines over time. We show that academic entrants have patents of lower ?quality? than academic incumbents but they did not cause the decline, since the relative importance of patents involving academics with an existing patenting history declined over time as well. Moreover, a preliminary evaluation of the effects of the abolishment of the ?professor privilege? (the German counterpart of the U.S. Bayh-Dole Act) reveals that this legal disposition led to an acceleration of this apparent decline.
Keywords: O32; O34; O31; 330; academic inventors; faculty patenting; patent quality; Öffentliche Forschung; Hochschulforschung; Patentrecht; Erfindung; Produktqualität; Patent; Wissenstransfer; Publikationsanalyse; Deutschland